Variable-diameter deep mixing column for multi-layered soft ground improvement : laboratory modeling and field application - Yi Yaolin (2020)
Deep mixing columns are commonly employed for soft ground improvement. However, the diameter of a single conventional column is a constant and the area replacement ratio does not vary with depth. Hence, the conventional column is not the ideal solution for multi-layered soft grounds, where different layers have remarkably different soil properties. Accordingly, this study proposes a better solution, which is the variable-diameter deep mixing column with a large diameter in the soil layer having high compressibility and a small diameter in the soil layer having relatively low compressibility. In this study, small-scale laboratory model tests were firstly employed to compare the performance of two-layered soft grounds improved by a variable-diameter column and a conventional column. The additional vertical stress in the soil and the column, the excess pore water pressure, and the ground settlement were analyzed. Then, a field application of variable-diameter columns for multi-layered soft ground improvement was presented; the design considerations, column installation, and monitored settlement were introduced and analyzed. The results indicated that the additional stress in the soil and the column in the highly compressible soil layer were much lower in the variable-diameter column-improved ground than in the conventional column-improved ground. Consequently, the variable-diameter column-improved ground yielded less total settlement and less post-construction settlement compared to the conventional column-improved ground.